1998
DOI: 10.1074/jbc.273.36.23558
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Open Complex Formation by Nicks and Apurinic Sites Suggests a Role for Nucleation of DNA Melting in Escherichia coli Promoter Function

Abstract: We report the effects of depurination and prenicking at various positions of the phage prmup-1⌬265 promoter DNA on the rate of open complex formation. We have found that depurination and prenicking at positions around the ؊10 region strongly stimulated the rate of open complex formation. Since nicking and depurination are known to destabilize DNA helical structure, our observations indicate that the instability of the ؊10 region is important for open complex formation. We further infer that (i) the nucleation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 43 publications
6
30
0
Order By: Relevance
“…The Ϫ11 position did not accept a pyrimidine base (cytosine or thymine) either, suggesting a strict requirement of an adenine or a purine at Ϫ11 (Table I). Our observation of the essential nature of a purine base with an unmodified C2 hydrogen at Ϫ11 for promoter activity is consistent with a previous report that depurination of adenine, while stimulating open complex formation when at position Ϫ12, Ϫ10, or ϩ1, inhibited the process when at position Ϫ11 (28).…”
Section: Role Of C2 Hydrogen Of Adenine At ϫ11 In Promoter Openingsupporting
confidence: 80%
See 1 more Smart Citation
“…The Ϫ11 position did not accept a pyrimidine base (cytosine or thymine) either, suggesting a strict requirement of an adenine or a purine at Ϫ11 (Table I). Our observation of the essential nature of a purine base with an unmodified C2 hydrogen at Ϫ11 for promoter activity is consistent with a previous report that depurination of adenine, while stimulating open complex formation when at position Ϫ12, Ϫ10, or ϩ1, inhibited the process when at position Ϫ11 (28).…”
Section: Role Of C2 Hydrogen Of Adenine At ϫ11 In Promoter Openingsupporting
confidence: 80%
“…Although these amino acid residues were shown to strategically lie on one face of the subunit to be able to perform the two functions in open complex formation, RNA polymerase binding and DNA deformation (10,11), the details of the interactions from structural viewpoints remain unknown. Studies of transcription initiation with specifically designed DNA templates suggested that DNA deformation nucleates at around position Ϫ10/Ϫ11 (9,(25)(26)(27)(28). The omnipresent A:T base pair at the position Ϫ11 was specifically suggested to play a "master" role in signaling DNA deformation (29).…”
mentioning
confidence: 99%
“…These results suggest that unpairing of the invariant A⅐T base pair Ϫ11 is a forerunner event and acts as the ''master'' of unpairing of bases. It has been suggested that DNA ''melting'' by RNA polymerase starts with a nucleation in the Ϫ12 to Ϫ4 region and extends up to ϩ2 position downstream (18). Our finding of Ϫ11 A⅐T being the master position further pinpoints the actual start of the process of the nucleation.…”
Section: Resultsmentioning
confidence: 55%
“…The consensus DNA sequence of the Ϫ10 region is 5Ј-TATAAT-3Ј in the nontemplate strand, with the first T being at the Ϫ12 position (1). To elucidate the molecular procedures of base unpairing during open complex formation, altered forms of DNA (depurinated, nicked, forked, or with single-stranded gap) in the Ϫ10 region were used as templates (10,(14)(15)(16)(17)(18)(19). These studies suggested that base unpairing involves an initial distortion or localized melting event around Ϫ11 (16,20).…”
Section: U Nder Ordinary Physiological Conditions Transcription Inmentioning
confidence: 99%
“…Measurement of the size and location of the region of strand separation as a function of temperature shows that at low temperatures a small single-stranded region can be detected that, as the temperature is increased, expands toward the start site (3,(5)(6)(7). In addition, the introduction of nicks and mismatches in the Ϫ10 region is more effective in the acceleration of open complex formation than if such distortions are introduced at a more downstream position (8,9).…”
Section: From the Department Of Biochemistry Case Western Reserve Unmentioning
confidence: 99%